In Vivo Translation and Stability of Trans-Spliced mRNAs in Nematode Embryos - Cheng, Guofeng (2007)
Spliced leader trans-splicing adds a short exon, the spliced leader (SL), to pre-mRNAs to generate 5’ ends of mRNAs. Addition of the SL in metazoa also adds a new cap to the mRNA, a trimethylguanosine (m(3)(2,2,7)GpppN)(TMG) that replaces the typical eukaryotic monomethylguanosine (m(7)GpppN)(m(7)G) cap. Both trans-spliced (m(3)(2,2,7)GpppN-SL-RNA) and not trans-spliced (m(7)GpppN-RNA) mRNAs are present in the same cells. Previous studies using cell-free systems to compare the overall translation of trans-spliced vs. non-trans-spliced RNAs led to different conclusions. Here we examine the contribution of m(3)(2,2,7)GpppG-cap and SL sequence and other RNA elements to in vivo mRNA translation and stability in nematode embryos. Although 70–90% of all nematode mRNAs have a TMG-cap, the TMG cap does not support translation as well as an m(7)G-cap. However, when the TMG cap and SL are present together, they synergistically interact and translation is enhanced, indicating both trans-spliced elements are necessary to promote efficient translation. The SL by itself does not act as a cap-independent enhancer of translation. The poly(A)-tail synergistically interacts with the mRNA cap enhancing translation and plays a greater role in facilitating translation of TMG-SL mRNAs. In general, recipient mRNA sequences between the SL and AUG and the 3’ UTR do significantly contribute to the translation of trans-spliced mRNAs. Overall, the combination of TMG cap and SL contribute to mRNA translation and stability in a manner typical of a eukaryotic m(7)G-cap and 5’ UTRs, but they do not differentially enhance mRNA translation or stability compared to RNAs without the trans-spliced elements.